A measurement error approach to the study of poverty - Nicoletta Rosati (Institute for Fiscal Studies (IFS), 2001)
This study investigates the pattern of poverty in Italy in the 1980s and the 1990s, by means of both eonsumption and ineome measures, so as to separate the permanent and temporary eomponents. The empirie al analysis we eonduet addresses not only eeonomie issues, but also those of survey methodology and reliability of data. The model for the study of poverty is inspired by the literat ure on measurement error, and allows us not only to identify the two eomponents but also to test if the varianees of the shoeks vary along the distributions of ineome and eonsumption. We find a slight inerease of the transitory eomponent, whereas the permanent one remains eonstant over the two decades. There is some evidenee of noneonstancy of the varianees of the shocks, and a more precise formal test is under development.
Keywords: D12; D31; I32; J31; 330; Income and consumption poverty; measurement error; permanent and transitory shocks; Armut; Messung; Schätzung; Italien